Development of a Vascularized Skin Construct Using Adipose-Derived Stem Cells from Debrided Burned Skin - Rodney K. Chan; David O. Zamora; Nicole L. Wrice; David G. Baer; Evan M. Renz; Robert J. Christy; Shanmugasundaram Natesan (Hindawi Limited, 2012)
Large body surface area burns pose significant therapeutic challenges. Clinically, the extent and depth of burn injury may mandate the use of allograft for temporary wound coverage while autografts are serially harvested from the same donor areas. The paucity of donor sites in patients with burns involving large surface areas highlights the need for better skin substitutes that can achieve early and complete coverage and retain normal skin durability with minimal donor requirements. We have isolated autologous stem cells from the adipose layer of surgically debrided burned skin (dsASCs), using a point-of-care stem cell isolation device. These cells, in a collagen-polyethylene glycol fibrin-based bilayer hydrogel, differentiate into an epithelial layer, a vascularized dermal layer, and a hypodermal layer. All-trans-retinoic acid and fenofibrate were used to differentiate dsASCs into epithelial-like cells. Immunocytochemical analysis showed a matrix- and time-dependent change in the expression of stromal, vascular, and epithelial cell markers. These results indicate that stem cells isolated from debrided skin can be used as a single autologous cell source to develop a vascularized skin construct without culture expansion or addition of exogenous growth factors. This technique may provide an alternative approach for cutaneous coverage after extensive burn injuries.